The global multidimensional poverty index (MPI) 2021 - Alkire, S; Kanagaratnam, U; Suppa, N (Oxford Poverty and Human Development Initiative (OPHI), 2021)
This 51st Methodological Note presents the methodology and technical decisions behind the global Multidimensional Poverty Index (MPI) 2021 and the results presented in Tables 1–8. This document is part of OPHI MPI Methodological Notes series. A Methodological Note is published for every release of the global MPI.